Exploration of indigenous soil bacteria producing-exopolysaccharides for stabilizing of aggregates land potential as biofertilizer - N Arfarita; N Hidayati; A Rosyidah; M Machfudz; T Higuchi (Brawijaya University, 2016)
Steady soil aggregationis important for agricultural land which is formed by the micro-aggregate to become a macro-aggregate. This formation is mediated by organic material and various kinds of macro-organisms such as fungi, worms, ants and insects. An organic agencyinvolved in soil aggregation stabilityis exopolysaccharide (EPS) derived from bacterial, fungal mycelium, and products synthesized by plants. However, the use of EPS producing microorganisms as a biofertilizer has not been reported. This study was aimedto explore indigenous EPS-producing bacteria to solidify soil aggregationpotential for biofertilizer. Bacterial strains were isolated from soilsofthree regions at Malang East-Java; two areas of green bean plantation in Kendal Payak and Jambe Gede, as well as forest land. Soil samplewas derived from forest had hasa total bacteria population of 9.3 x 1011 CFU/mL.While soil samples from area Kendal Payak and Jambe Gede had total bacteria population of 1.5 x 109 CFU/mL and 2.4 x 109 CFU/mL, respectively. We selected three bacteria that could potentially produce abundant slime, namely as SPE-2, SPE-10 and SPE-20. The three selected bacteria are potential for biofertilizer because oftheir abundant slime, no antagonism and no symtoms as pathogen.